PhyreStorm: A web server for fast structural searches against the PDB. - Mezulis,S; Sternberg,MJ; Kelley,LA (Journal of Molecular Biology, 2015)
The identification of structurally similar proteins can provide a range of biological insights and accordingly the alignment of a query protein to a database of experimentally-determined protein structures is a technique commonly used in the fields of structural and evolutionary biology. The PhyreStorm web server has been designed to provide comprehensive, up-to-date and rapid structural comparisons against the Protein Data Bank (PDB) combined with a rich and intuitive user interface. It is intended that this facility will enable biologists inexpert in bioinformatics access to a powerful tool for exploring protein structure relationships beyond what can be achieved by sequence analysis alone. By partitioning the PDB into similar structures, PhyreStorm is able to quickly discard the majority of structures that cannot possibly align well to a query protein, reducing the number of alignments required by an order of magnitude. PhyreStorm is capable of finding 93±2% of all highly similar (TM-score >0.7) structures in the PDB for each query structure, usually in under 60 seconds. PhyreStorm is available at http://www.sbg.bio.ic.ac.uk/phyrestorm/.